Analysis of sensor-debonding failure in active vibration control of smart composite plate. (November 2017) - Khan, Asif; Lee, Hyun Sung; Kim, Heung Soo
In this article, the effect of a sensor-debonding failure on the active vibration control of a smart composite plate is investigated numerically. A mathematical model of the smart structure with a partially debonded piezoelectric sensor is developed using an improved layerwise theory, a higher-order electric-potential field that serves as the displacement field, and the potential variation through the piezoelectric patches. A state-space form that is based on the reduced-order model is employed for the controller design. A control strategy with a constant gain and velocity feedback is used to assess the vibration-control characteristics of the controller in the presence of the sensor-debonding failure. The obtained results show that sensor-debonding failure reduces the sensor-output, control-input signal, and active damping in magnitude that successively degrades the vibration attenuation capability of the active vibration controller. The settling time and relative tip displacement of the controlled structure increase with the increasing length of partial debonding between the piezoelectric sensor and host structure. Furthermore, a damage-sensitive feature along with multidimensional scaling showed excellent results for the detection and quantification of sensor-debonding failure in the active vibration control of smart structures.